AKIBAT HUKUM PENCABUTAN LAPORAN TINDAK PIDANA PEMERASAN DAN ANCAMAN PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Rahmat Fauzi Fauzi; Sugianto (Universitas Islam Negeri Mataram, 2026)
The withdrawal of a criminal report by the victim in the crime of extortion and threat, which is motivated by consumer financing disputes, gives rise to different legal consequences under positive law and Islamic law. This study aims to analyze the legal consequences of withdrawing a report on the crimes of extortion and threat under Indonesian positive law, analyze its legal consequences from the perspective of Islamic law, and identify points of synchronization between the two legal systems. The research method employed is normative-empirical with statutory, case, and comparative approaches. The case study focuses on the dispute between Yudha Prasetya bin Yahya (reporter) and Budy Widjaja (reported party), which originated from the repossession of a motor vehicle collateral without the presence of the debtor with an arrears of two months (Rp8,020,000), which was subsequently resolved through a peace agreement consisting of joint unit sale (Rp120,000,000), debt repayment (Rp94,000,000), and the return of surplus funds of Rp26,000,000 to the debtor. The findings reveal that under positive law, the withdrawal of the report factually terminates the investigation process through the Issuance of the Investigation Termination Order (SP3) based on the principle of opportunity and Police Regulation No. 8 of 2021 concerning Restorative Justice, yet normatively it does not extinguish the material criminal act because the extortion offense (Article 368 of the Criminal Code) constitutes a general offense that may be revived should new evidence emerge. Under Islamic law, the withdrawal of the report accompanied by a peace agreement (sulh) and restitution eliminates all criminal claims (the annulment of ta'zir sanctions) and civil claims (the obligation of dhaman is deemed fulfilled), since this criminal act predominantly pertains to haqqul 'abdi (individual rights) that may be forgiven ('afwu) and reconciled (sulh) based on Qur'anic verse Surah An-Nisa: 128 and prophetic hadiths concerning peace. Both legal systems demonstrate alignment in respecting family-based dispute resolution and restorative justice, provided that the peace agreement is conducted without coercion, fraud, or error, and restores the victim's rights both materially and immaterially. This study recommends the necessity of harmonizing the provisions of complaint offenses in positive law with the principle of sulh in Islamic law in the renewal of national criminal law, as well as strengthening the collateral repossession protocols by financing companies to prevent such actions from entering the criminal domain.